Thermal adaptation of cellular membranes in natural populations of Drosophila melanogaster. (12th March 2014) - Cooper, Brandon S.; Hammad, Loubna A.; Montooth, Kristi L.; Wilson, Robbie
Summary Changes in temperature disrupt the fluidity of cellular membranes, which can negatively impact membrane integrity and cellular processes. Many ectotherms, including Drosophila melanogaster (Meigen), adjust the glycerophospholipid composition of their membranes to restore optimal fluidity when temperatures change, a type of trait plasticity termed homeoviscous adaptation. Existing data suggest that plasticity in the relative abundances of the glycerophospholipids phosphatidylethanolamine (PE) and phosphatidylcholine (PC) underlies cellular adaptation to temporal variability in the thermal environment. For example, laboratory populations of D. melanogaster evolved in the presence of temporally variable temperatures have greater developmental plasticity of the ratio of PE to PC (PE/PC) and greater fecundity than do populations evolved at constant temperatures. Here, we extend this work to natural populations of D. melanogaster by evaluating thermal plasticity of glycerophospholipid composition at different life stages, in genotypes isolated from Vermont, Indiana and North Carolina, USA. We also quantify the covariance between developmental and adult (reversible) plasticity, and between adult responses of the membrane to cool and warm thermal shifts. As predicted by physiological models of homeoviscous adaptation, flies from all populations decrease PE/PC and the degree of lipid unsaturation in response to warm temperatures. Furthermore, these populations have diverged in their degree of membrane plasticity. Flies from the most variable thermal environment (Vermont, USA) decrease PE/PC to a greater extent than do other populations when developed at a warm temperature, a pattern that matches our previous observation in laboratory‐evolved populations. We also find that developmental plasticity and adult plasticity of PE/PC covary across genotypes, but that adult responses to cool and warm thermal shifts do not. When combined with our previous observations of laboratory‐evolved populations, our findings implicate developmental plasticity of PE/PC as a mechanism of thermal adaptation in temporally variable environments. While little is known about the genetic bases of plastic responses to temperature, our observations suggest that both environmentally sensitive and environmentally specific alleles contribute to thermal adaptation of membranes and that costs of plasticity may arise when the adult environment differs from that experienced during development.